Multi-dimensional hydrogen bond conductive adhesive synthesized from natural polymer product and preparation method and application of multi-dimensional hydrogen bond conductive adhesive
By using peach gum polysaccharide and polyacrylic acid and adding a multi-dimensional hydrogen bond conductive adhesive with single-wall carbon nanotubes, the problems of poor conductivity of CVD silicon carbon negative electrode materials and uncontrollable solid electrolyte membrane are solved, and the cycle stability of the electrode is improved and electrochemical properties.
Patent Information
- Application Number
- CN202411394883.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2024-12-27
AI Technical Summary
The CVD silicon carbon anode material has a reduced conductivity due to the overlay of a large number of non-ordered carbon materials, and traditional binders cannot effectively control the growth of the solid electrolyte membrane, affecting the cyclic stability of the electrode.
The natural polymer product peach gum polysaccharide and polyacrylic acid (PAA) are blended into a multi-dimensional hydrogen bonding adhesive, and single-walled carbon nanotubes (SWCNT) are added to impart conductive capacity to form a PGP/PAA/SWCNT composite adhesive. Used to prepare silicon carbon electrodes.
It significantly improves the electron conductivity and cyclic stability of silicon carbon electrodes, enhances the control ability of the solid electrolyte membrane, and realizes a more efficient electrochemical energy storage system.
Smart Images

Figure CN119208611A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a multidimensional hydrogen bond conductive adhesive synthesized from a natural polymer product, and a preparation method and application thereof. Background Art
[0002] In the field of lithium-ion batteries, the performance of negative electrode materials directly determines the energy density, cycle stability and safety performance of the battery. The theoretical capacity of traditional graphite negative electrode materials is close to its theoretical limit, and it is difficult to meet the market demand for higher energy density batteries. Therefore, researchers have been looking for new negative electrode materials that can significantly improve battery performance. Silicon-based negative electrode materials have attracted much attention due to their high theoretical energy density (up to 4200mAh / g), but their huge volume expansion (about 320%) and low initial efficiency during charging and discharging have become the main obstacles to their commercial application.
[0003] To solve these problems, academia and industry have developed a variety of silicon-based negative electrode modification technologies, such as silicon oxidation, nano-sizing, composite, porosification, alloying, pre-lithiation and pre-magnesiation. For example, Chinese patent CN202410720058.7 provides a soft elastic binder A and polyacrylic acid (PAA) cross-linked to obtain a binder. However, this scheme still involves the synthesis of the binder, which requires a complex binder synthesis process. The method is complicated and not convenient and environmentally friendly. Chinese patent CN201810205727.1 discloses a cross-linked composite adhesive and its application, and a lithium-ion battery negative electrode material and preparation method prepared based on it. The patent uses boric acid to cross-link sodium alginate and fulvic acid to form an effective multidimensional binder. The multidimensional binder can interact with silicon particles through multidimensional hydrogen bonds, enhance the bonding force, prevent the silicon particles from pulverizing and falling off, and improve the battery cycle performance. However, although the binder has the functions of self-healing and elasticity, it does not have the ability to conduct electrons / ions, and is not suitable for silicon-carbon negative electrode materials prepared by the new CVD method. Chinese patent CN202010104392.1 discloses polyacrylate photocurable binders and their use in lithium-ion battery silicon negative electrode sheets. Polyacrylate photocurable binders, especially PUA photocurable binders, are used in lithium battery silicon negative electrodes. In the field of lithium-ion battery silicon negative electrodes, UV in-situ crosslinking is used. Compared with the methods used in previous battery production binders, UV in-situ crosslinking binders have better bonding performance and a deeper and denser crosslinking network, which is conducive to the improvement of conductivity and packing density, and the formation of a crosslinking network between the current collector and the active material, and the improvement of energy density. However, the photocuring system results in no dynamic hydrogen bond crosslinking in the system, the electrode lacks self-healing ability, and the growth of silicon solid electrolyte membrane (SEI) cannot be effectively controlled.
[0004] Among them, US Patent US20240047650A1 is a CVD silicon-carbon negative electrode material developed by Group14 Technologies in the United States. The negative electrode material has a low expansion effect. The technology uses the chemical reaction of silane and hydrocarbons at high temperature to prepare a silicon-carbon composite material with high gram capacity, excellent cycle performance and high first efficiency. However, the CVD silicon-carbon negative electrode is covered by a large amount of non-ordered carbon material, which leads to a decrease in its conductivity; and the special structure makes the sodium carboxymethyl cellulose / styrene-butadiene rubber binder system commonly used in industry unsuitable for it. Chemical vapor deposition (CVD) technology has become a research hotspot due to its unique advantages in the preparation of silicon-carbon composite materials. CVD technology can achieve precise control of the microstructure and composition of the material by using gaseous or vapor precursors to react chemically in a substrate or space to generate solid products under specific conditions. The CVD silicon-carbon negative electrode material SCC5 developed by Group14 Technologies in the United States effectively suppresses the volume expansion of silicon during lithium insertion by depositing silicon nanoparticles in a porous carbon skeleton. This technology uses the chemical reaction of silane and hydrocarbons at high temperature to prepare silicon-carbon composite materials with high gram capacity, excellent cycle performance and high initial efficiency, providing new possibilities for the commercialization of lithium battery negative electrode materials.
[0005] However, since the CVD silicon-carbon anode is covered by a large amount of non-ordered carbon materials, its conductivity has decreased. At the same time, the high rigidity of polyacrylic acid (PAA), which is widely used in industry as a binder, also makes the solid electrolyte interface (SEI) of the silicon-carbon anode easy to break and reform repeatedly, thus affecting the cycle stability of the electrode. Summary of the invention
[0006] In order to solve the above technical problems, the present invention proposes a multidimensional hydrogen-bonded conductive adhesive synthesized from a natural polymer product, a preparation method and an application thereof. A multidimensional hydrogen-bonded adhesive network is constructed by blending a natural polymer product peach gum polysaccharide (PGP) with an industrially commonly used PAA adhesive, and then a small amount of single-walled carbon nanotube (SWCNT) is added to give the adhesive network strong conductivity, thereby solving the problems of poor electronic conductivity of CVD silicon-carbon negative electrode and uncontrollable SEI.
[0007] To achieve the above object, the present invention provides a multidimensional hydrogen-bonded conductive adhesive synthesized from a natural polymer product. The multidimensional hydrogen-bonded conductive adhesive is prepared from a peach gum polysaccharide solution, a PAA solution and a SWCNT solution according to a mass ratio of peach gum polysaccharide:PAA:SWCNT of (1-6):(1-6):(1-2).
[0008] The present invention also provides a method for preparing the multidimensional hydrogen bond conductive adhesive, comprising the following steps: (1) Soak peach gum in water until it is completely swollen, adjust the pH to 11-13, hydrolyze, concentrate by rotary evaporation to 20-35% of the original volume, and dialyze to obtain peach gum polysaccharide solution; (2) dissolving PAA in deionized water to obtain a PAA solution; (3) The peach gum polysaccharide solution of step (1), the PAA solution of step (2) and the SWCNT solution are mixed according to a mass ratio and stirred to obtain a multidimensional hydrogen bond conductive adhesive.
[0009] Preferably, the hydrolysis temperature in step (1) is 80-100° C., the hydrolysis time is 10-14 h, the hydrolysis promoter is H2O2, and the hydrolysis is carried out under continuous stirring; the rotation speed of the rotary evaporation concentration in step (1) is 10-180 rpm, the rotary evaporation concentration temperature is 30-40° C., and the rotary evaporation concentration time is 5-10 h; the dialysis in step (1) is carried out using a dialysis bag with a molecular weight cutoff of 14000-50000 Da; the mass concentration of the peach gum polysaccharide solution in step (1) is 10-14%.
[0010] Preferably, the molecular weight of PAA in step (2) is 1000-450000 g / mol; and the mass concentration of the PAA solution in step (2) is 10-20%.
[0011] Preferably, in the SWCNT solution in step (3), the average diameter of the SWCNT is 2-15 nm, the length of the SWCNT is ≥100 μm, and the specific surface area of the SWCNT is ≥450 m 2 / g; the solid content of the SWCNT solution in step (3) is 4%.
[0012] Preferably, the stirring speed in step (3) is 500-3000 rpm, and the stirring time is 10-14 h.
[0013] The present invention also provides application of the multi-dimensional hydrogen bond conductive adhesive in preparing a silicon-carbon electrode.
[0014] The present invention also provides a method for preparing a silicon-carbon electrode using the multidimensional hydrogen-bonded conductive binder, comprising the following steps: S1. Dispersing the novel CVD silicon-carbon negative electrode material, the multidimensional hydrogen bond conductive binder and the conductive carbon black in 3-20 mL of water in a mass ratio of (60-85): (10-20): (5-20) to obtain a mixture; S2, coating the mixture in S1 on a copper foil current collector to obtain a pretreated electrode; S3. The pretreated electrode described in S2 is subjected to vacuum drying to obtain a silicon-carbon electrode.
[0015] Preferably, the conductive carbon black in S1 is acetylene black or Super P; the coating thickness of the mixture in S2 is 100-150 μm, and the coating interval is 50-200 μm.
[0016] Preferably, the vacuum degree of the vacuum drying in S3 is -60 to -100 kPa, the temperature of the vacuum drying is 60 to 150° C., and the time of the vacuum drying is 1 to 12 h.
[0017] Compared with the prior art, the present invention has the following advantages and technical effects: The present invention discloses a multidimensional hydrogen-bonded conductive binder synthesized from a natural polymer product. The design of the binder aims to optimize the electronic conductivity of the electrode and enhance the cycle stability of the electrode by precisely regulating the formation of a solid electrolyte interface (SEI) film. This can significantly improve the overall performance of the electrode and realize a more efficient electrochemical energy storage system.
[0018] (1) The silicon-carbon electrode prepared by the present invention using a multidimensional hydrogen-bonded conductive binder effectively overcomes the shortcomings of the new CVD silicon-carbon material itself, which has poor conductivity and uncontrollable growth of the SEI film; the silicon-carbon electrode of the present invention has a high first coulombic efficiency, a long cycle stability and excellent rate performance.
[0019] (2) Compared with the use of each component alone, PGP is too soft and cannot withstand the huge volume strain generated by silicon particles during the charge and discharge process; PAA is too rigid, and the silicon-carbon particles lose contact with the copper foil after cycling, resulting in electrode failure; PGP / PAA composite effectively combines flexibility and rigidity, and the rigid-flexible binder can withstand the volume strain of silicon during charge and discharge, but the new CVD silicon-carbon material particles are large and coated with disordered carbon materials, resulting in poor ion / electron conductivity. The PGP / PAA / SWCNT composite binder of the present invention tightly attaches silicon and conductive agent to copper foil, preventing the separation of electrode components during charge and discharge, and can provide a fast electron / ion transmission channel to effectively improve the cycle stability of the silicon negative electrode.
[0020] (3) PGP / PAA jointly construct a multidimensional hydrogen bond interaction, which allows the macromolecular PAA chain to be stretched; during the electrode preparation process, the active material, binder, and conductive agent components can be effectively mixed evenly, effectively improving the electrode dispersibility.
[0021] (4) The present invention uses PGP as one of the raw materials to introduce a large number of active hydroxyl groups, promote hydrogen bond cross-linking, and enable the entire electrode to obtain the ability of dynamic self-healing fracture cracks, thereby maintaining the integrity of the electrode sheet.
[0022] (5) The preparation of the silicon-carbon electrode described in the present invention can be completed with water. In addition, PGP is a natural polymer material. Compared with the polyvinylidene fluoride / nitrogen-methylpyrrolidone system for traditional electrode preparation, it has the advantages of being environmentally friendly, non-toxic, harmless, having a wide range of raw material sources, and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 The electron microscope images and energy spectrum of the SC@GPS electrode prepared in Example 1, wherein A is the electron microscope image of the CVD silicon-carbon overall appearance, with a scale of 5 μm; B is the elemental layered image of the CVD silicon-carbon overall appearance electron microscope image, with a scale of 5 μm; C is the Si element distribution image of the CVD silicon-carbon overall appearance electron microscope image, with a scale of 5 μm; D is the C element distribution image of the CVD silicon-carbon overall appearance electron microscope image, with a scale of 5 μm; E is the O element distribution image of the CVD silicon-carbon overall appearance electron microscope image Layout, scale is 5μm; F is the electron microscope image of a CVD silicon-carbon single particle, scale is 10μm; G is the element layering image of the electron microscope image of a CVD silicon-carbon single particle, scale is 10μm; H is the Si element distribution image in the electron microscope image of a CVD silicon-carbon single particle, scale is 10μm; I is the C element distribution image in the overall electron microscope image of CVD silicon-carbon, scale is 10μm; J is the O element distribution image in the overall electron microscope image of CVD silicon-carbon, scale is 10μm; Figure 2 The present invention is a flow chart of the preparation of silicon carbon electrode; Figure 3 The average peel strength measurement diagram of the silicon-carbon electrodes prepared in Example 1 and Comparative Examples 1 to 4, wherein A is a peel force curve diagram and B is an average peel force; Figure 4 The graphs are the nanoindentation test results of the silicon-carbon electrodes prepared in Example 1 and Comparative Examples 1 to 4, wherein A is the nanoindentation curve graph, and B is the hardness and relative elastic modulus; Figure 5 The graphs are the cycle performance and first coulomb efficiency measurement graphs of the silicon-carbon electrodes prepared in Example 1 and Comparative Examples 1 to 4, wherein A is the cycle performance measurement graph, and B is the first coulomb efficiency measurement graph. DETAILED DESCRIPTION
[0025] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0026] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0027] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0028] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0029] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0030] Sources of materials used in the present invention: peach gum was purchased from Cangzhou Kunlin Wax Co., Ltd.; PAA was purchased from Guangdong Qianjin Chemical Reagent Co., Ltd.; SWCNT solution was purchased from Jiangsu Tiannai Technology Co., Ltd., with a solid content of 4%; porous activated carbon material was purchased from Zhejiang Apex Energy Technology Co., Ltd.; monosilane, disilane, hexamethyldisilane, chlorosilane and tetrafluorosilane were all purchased from Zhejiang Zhongning Silicon Co., Ltd.; methane, ethane, ethylene, acetylene and propylene were all purchased from Guangxi Hengyu Gas Co., Ltd.; acetylene black was purchased from TIMCAL; Super P was purchased from TIMCAL.
[0031] Example 1
[0032] Preparation of multidimensional hydrogen-bonded conductive adhesives: (1) 6 g of dried peach gum was soaked in 100 mL of deionized water for 24 h until the peach gum was completely swollen. The pH was adjusted to 12 with a 1 M NaOH solution, and 3 mL of hydrolysis promoter H2O2 was added. The mixture was hydrolyzed at 90 °C for 12 h under continuous stirring. The mixture was concentrated by rotary evaporation at a speed of 95 rpm and a temperature of 35 °C for 7.5 h to 30% of the original volume. The solution was dialyzed using a dialysis bag with a molecular weight cutoff of 32,000 Da to obtain a peach gum polysaccharide solution with a mass concentration of 12%. (2) The preparation steps of the PAA solution are as follows: 1 g of PAA (prepared with PAA having a molecular weight of 450,000 g / mol) is dissolved in 9 g of deionized water to obtain a PAA solution having a mass concentration of 10%; (3) Peach gum polysaccharide solution, PAA solution and SWCNT solution with a solid content of 4% (the average tube diameter of SWCNT in the SWCNT solution is 8nm and the specific surface area is ≥450m 2 / g, length ≥100μm) were mixed according to the mass ratio of peach gum polysaccharide:PAA:SWCNT of 4.5:4.5:1 and stirred at 2000rpm for 12h to obtain a multidimensional hydrogen bond conductive adhesive.
[0033] Method for preparing silicon carbon electrode: The new CVD silicon-carbon anode material was prepared by fluidized bed method with a particle size of 8 μm and a specific surface area of 2000 m 2 / g, 1300g of porous activated carbon material with a pore size of 1~2nm was placed in a stirred fluidized bed reactor into which a mixed gas of 13L nitrogen and 3L monosilane was introduced, and the flow rate of the mixed gas in the reactor was 0.001~10m / s, and silicon deposition was performed at 520℃ for 484min to obtain a silicon-based intermediate. Subsequently, a mixed gas of 3L acetylene and 15L nitrogen was introduced, and the flow rate of the mixed gas of acetylene and nitrogen in the reactor was 0.001~10m / s, and the silicon-based intermediate was coated at 580℃ for 200min to obtain a new CVD silicon-carbon negative electrode material.
[0034] S1. Disperse the novel CVD silicon-carbon negative electrode material, the multidimensional hydrogen-bonded conductive binder and Super P in 10 mL of deionized water in a mass ratio of 85:10:5, fully mix them in a high-speed oscillating ball mill, and thin the slurry by shearing to obtain a mixture; S2. The mixture is coated on a copper foil current collector with a coating distance of 150 μm and a thickness of 125 μm using a doctor blade with adjustable thickness to obtain a pretreated electrode; S3, pre-treat the electrode, dry it at 60℃ for 6h, and then vacuum dry it at -80kpa and 120℃ for 12h to evaporate the water to obtain a silicon-carbon electrode. The prepared silicon-carbon PGP / PAA / SWCNT electrode is named SC@GPS electrode. Figure 1As shown in FIG. 1 , the electron microscope image and energy spectrum of the SC@GPS electrode prepared in this example are shown in FIG. Figure 2 The figure shows the process of preparing silicon carbon electrode.
[0035] Example 2
[0036] Preparation of multidimensional hydrogen-bonded conductive adhesives: (1) 6 g of dried peach gum was soaked in 100 mL of deionized water for 24 h until the peach gum was completely swollen. The pH was adjusted to 11 with a 1 M KOH solution, and 3 mL of hydrolysis promoter H2O2 was added. The mixture was hydrolyzed at 80 °C for 14 h under continuous stirring. The mixture was concentrated by rotary evaporation at a speed of 10 rpm and a temperature of 30 °C for 10 h to 35% of the original volume. The solution was dialyzed using a dialysis bag with a molecular weight cutoff of 14,000 Da to obtain a peach gum polysaccharide solution with a mass concentration of 10%. (2) The preparation steps of the PAA solution are as follows: 1 g of PAA (prepared with PAA having a molecular weight of 1000 g / mol) is dissolved in 9 g of deionized water to obtain a PAA solution having a mass concentration of 10%; (3) Peach gum polysaccharide solution, PAA solution and SWCNT solution with a solid content of 4% (the average tube diameter of SWCNT in the SWCNT solution is 8nm and the specific surface area is ≥450m 2 / g, length ≥100μm) were mixed according to the mass ratio of peach gum polysaccharide:PAA:SWCNT of 6:3:1 and stirred at 500rpm for 14h to obtain a multidimensional hydrogen bond conductive adhesive.
[0037] Method for preparing silicon carbon electrode: The new CVD silicon-carbon anode material was prepared by fluidized bed method with a particle size of 8 μm and a specific surface area of 2000 m 2 / g, 1300g of porous activated carbon material with a pore size of 1~2nm was placed in a stirred fluidized bed reactor into which a mixed gas of 13L nitrogen and 3L monosilane was introduced, and the flow rate of the mixed gas in the reactor was 0.001~10m / s, and silicon deposition was performed at 520℃ for 484min to obtain a silicon-based intermediate. Subsequently, a mixed gas of 3L methyl ene and 15L nitrogen was introduced, and the flow rate of the mixed gas of acetylene and nitrogen in the reactor was 0.001~10m / s, and the silicon-based intermediate was coated at 580℃ for 200min to obtain a new CVD silicon-carbon negative electrode material.
[0038] S1. Disperse the novel CVD silicon-carbon negative electrode material, the multidimensional hydrogen-bonded conductive binder and Super P in 3 mL of deionized water in a mass ratio of 85:10:5, fully mix them in a high-speed oscillating ball mill, and thin the slurry by shearing to obtain a mixture; S2. The mixture is coated on a copper foil current collector with a coating distance of 50 μm and a thickness of 100 μm using a doctor blade with adjustable thickness to obtain a pretreated electrode; S3. Pre-treat the electrode, dry it at 60°C for 6 hours, then perform vacuum drying at -60 kPa and 60°C for 12 hours to evaporate the water to obtain a silicon-carbon electrode.
[0039] Example 3
[0040] Preparation of multidimensional hydrogen-bonded conductive adhesives: (1) 6 g of dried peach gum was soaked in 100 mL of deionized water for 24 h until the peach gum was completely swollen. The pH was adjusted to 13 with a 1 M NaOH solution, and 3 mL of hydrolysis promoter H2O2 was added. The mixture was hydrolyzed at 100 °C for 10 h under continuous stirring. The solution was concentrated by rotary evaporation at a speed of 180 rpm and a temperature of 40 °C for 5 h to 20% of the original volume. The solution was dialyzed using a dialysis bag with a molecular weight cutoff of 50,000 Da to obtain a peach gum polysaccharide solution with a mass concentration of 14%. (2) The preparation steps of the PAA solution are as follows: 1 g of PAA (prepared with PAA having a molecular weight of 450,000 g / mol) is dissolved in 9 g of deionized water to obtain a PAA solution having a mass concentration of 10%; (3) Peach gum polysaccharide solution, PAA solution and SWCNT solution with a solid content of 4% (the average tube diameter of SWCNT in the SWCNT solution is 8nm and the specific surface area is ≥450m 2 / g, length ≥100μm) were mixed according to the mass ratio of peach gum polysaccharide:PAA:SWCNT of 3:6:1 and stirred at 3000rpm for 10h to obtain a multidimensional hydrogen bond conductive adhesive.
[0041] Method for preparing silicon carbon electrode: The new CVD silicon-carbon anode material was prepared by fluidized bed method with a particle size of 8 μm and a specific surface area of 2000 m 2 / g, 1300g of porous activated carbon material with a pore size of 1~2nm was placed in a stirred fluidized bed reactor into which a mixed gas of 13L nitrogen and 3L disilane was introduced, and the flow rate of the mixed gas in the reactor was 0.001~10m / s, and silicon deposition was performed at 520℃ for 484min to obtain a silicon-based intermediate. Subsequently, a mixed gas of 3L ethane and 15L nitrogen was introduced, and the flow rate of the mixed gas of acetylene and nitrogen in the reactor was 0.001~10m / s, and the silicon-based intermediate was coated at 580℃ for 200min to obtain a new CVD silicon-carbon negative electrode material.
[0042] S1. Disperse the novel CVD silicon-carbon negative electrode material, the multidimensional hydrogen-bonded conductive binder and Super P in 20 mL of deionized water in a mass ratio of 85:10:5, fully mix them in a high-speed oscillating ball mill, and thin the slurry by shearing to obtain a mixture; S2, the mixture is coated on a copper foil current collector with a coating distance of 200 μm and a thickness of 150 μm using a doctor blade with adjustable thickness to obtain a pretreated electrode; S3. Pre-treat the electrode, dry it at 60°C for 6 hours, then vacuum dry it at -100 kPa and 150°C for 1 hour to evaporate the water to obtain a silicon-carbon electrode.
[0043] Comparative Example 1
[0044] The difference from Example 1 is that the peach gum polysaccharide solution, the PAA solution and the SWCNT solution are mixed in a mass ratio of peach gum polysaccharide:PAA:SWCNT of 5:5:0, and the silicon-carbon electrode finally prepared is named SC@GP electrode.
[0045] Comparative Example 2
[0046] The difference from Example 1 is that the peach gum polysaccharide solution, the PAA solution and the SWCNT solution are mixed in a mass ratio of peach gum polysaccharide:PAA:SWCNT of 9:0:1, and the silicon carbon electrode finally prepared is named SC@PS electrode.
[0047] Comparative Example 3
[0048] The difference from Example 1 is that the peach gum polysaccharide solution, the PAA solution and the SWCNT solution are mixed in a mass ratio of peach gum polysaccharide:PAA:SWCNT of 10:0:0, and the silicon carbon electrode finally prepared is named SC@P electrode.
[0049] Comparative Example 4
[0050] The difference from Example 1 is that the peach gum polysaccharide solution, the PAA solution and the SWCNT solution are mixed in a mass ratio of peach gum polysaccharide:PAA:SWCNT of 0:10:0, and the silicon carbon electrode finally prepared is named SC@G electrode.
[0051] Experimental Example 1
[0052] 1. Average peel strength test of silicon carbon electrode
[0053] The peel strength of SC@GPS, SC@GP, SC@PS, SC@G and SC@P was tested. The peel strength of the electrode was measured on a universal tensile machine: the tape attached to the electrode was pulled at a speed of 10 mm / min, and the force-displacement diagram was obtained to calculate the average peel strength.
[0054] The results are as follows Figure 3 Middle A and Figure 3 As shown in Figure B, the average adhesion of SC@GPS, SC@GP, SC@PS, SC@G and SC@P is 4.96N, 5.25N, 4.11N, 4.18N and 3.26N, respectively. The peel strength difference between SC@GPS and SC@GP electrodes is not large, and the peel strength difference between SC@PS and SC@P electrodes is also not large. It can be seen that the addition of SWCNT does not change the mechanical properties of the electrode. Due to the addition of PGP, a hydrogen bond cross-linking network is constructed, which gives the electrode higher cohesion and stronger adhesion. Higher bonding strength has great advantages in dealing with the huge volume changes during the charging and discharging process of silicon-carbon materials.
[0055] 2. Electrode stress resistance test
[0056] Nanoindentation tests were performed on SC@GPS, SC@GP, SC@PS, SC@G, and SC@P electrodes using a nanoindentation tester to evaluate the mechanical properties of different binders. The maximum load of the nanoindentation test was 1 mN, using a Berkovich indenter. The elastic modulus and hardness of the different electrodes were calculated using the Oliver-Pharr method.
[0057] The results are as follows Figure 4 Middle A and Figure 4 As shown in Figure B, since the peel strength test results show that the addition of SWCNT does not change the mechanical properties of the electrode, it is only necessary to compare the stress resistance of SC@GP, SC@G and SC@P electrodes. The experimental results show that the SC@GP electrode has the shallowest indentation depth. This is because the SC@GP electrode has both the rigidity of PAA and the flexibility of PGP. The construction of multiple hydrogen bonds makes the SC@GP electrode both strong and elastic, and can well cope with the stress generated by the volume strain of the material.
[0058] 3. Electrochemical performance test
[0059] The CR2032 button cells assembled with SC@GPS, SC@GP, SC@PS, SC@G and SC@P were charged and discharged by constant current method at 25℃ and 0.01~1.5V vs Li / Li + The specific capacity of the silicon electrode during the charge and discharge process was measured to obtain the first coulombic efficiency and cycle performance (expressed by the discharge specific capacity after 100 cycles at 0.5C) for stability testing.
[0060] The results are as follows Figure 5 Middle A and Figure 5As shown in Figure B, the SC@G and SC@P electrodes without SWCNTs cannot withstand long-term charge and discharge cycles due to poor mechanical properties and conductivity. The SC@GP and SC@PS electrodes only have one of the mechanical and conductive properties. The cycle performance is improved compared to the SC@G and SC@P electrodes, but the capacity reduction trend is still obvious. The SC@GPS electrode has both conductivity and mechanical properties, so it exhibits the highest first coulombic efficiency (90.75%) and stable cycle performance, and still maintains a discharge specific capacity of 1875mAh / g after 100 cycles.
[0061] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A multi-dimensional hydrogen-bonded conductive adhesive synthesized from a natural polymer product, characterized in that: The multidimensional hydrogen bond conductive adhesive is prepared from peach gum polysaccharide solution, PAA solution and SWCNT solution according to the mass ratio of peach gum polysaccharide:PAA:SWCNT of (1-6):(1-6):(1-2).
2. The method for preparing the multidimensional hydrogen bond conductive adhesive according to claim 1, characterized in that: The following steps are involved: (1) Soak peach gum in water until it is completely swollen, adjust the pH to 11-13, hydrolyze, concentrate by rotary evaporation to 20-35% of the original volume, and dialyze to obtain peach gum polysaccharide solution; (2) dissolving PAA in deionized water to obtain a PAA solution; (3) The peach gum polysaccharide solution of step (1), the PAA solution of step (2) and the SWCNT solution are mixed according to a mass ratio and stirred to obtain a multidimensional hydrogen bond conductive adhesive.
3. The preparation method according to claim 2, characterized in that: The hydrolysis temperature in step (1) is 80-100° C., the hydrolysis time is 10-14 hours, the hydrolysis promoter is H2O2, and the hydrolysis is carried out under continuous stirring; the rotation speed of the rotary evaporation concentration in step (1) is 10-180 rpm, the rotary evaporation concentration temperature is 30-40° C., and the rotary evaporation concentration time is 5-10 hours; the dialysis in step (1) is carried out using a dialysis bag with a molecular weight cutoff of 14000-50000 Da; the mass concentration of the peach gum polysaccharide solution in step (1) is 10-14%.
4. The preparation method according to claim 2, characterized in that: The molecular weight of PAA in step (2) is 1000-450000 g / mol; the mass concentration of the PAA solution in step (2) is 10-20%.
5. The preparation method according to claim 2, characterized in that: The average diameter of the SWCNT in the SWCNT solution in step (3) is 2-15 nm, the length of the SWCNT is ≥100 μm, and the specific surface area of the SWCNT is ≥450 m 2 / g; the solid content of the SWCNT solution in step (3) is 4%.
6. The preparation method according to claim 2, characterized in that: The stirring speed in step (3) is 500-3000 rpm, and the stirring time is 10-14 h.
7. Use of the multidimensional hydrogen-bonded conductive adhesive as claimed in claim 1 or the multidimensional hydrogen-bonded conductive adhesive prepared by the preparation method according to any one of claims 2 to 6 in the preparation of silicon-carbon electrodes.
8. A method for preparing a silicon-carbon electrode using the multidimensional hydrogen-bonded conductive adhesive according to claim 1 or the multidimensional hydrogen-bonded conductive adhesive prepared by the preparation method according to any one of claims 2 to 6, characterized in that: The following steps are involved: S1. Dispersing the novel CVD silicon-carbon negative electrode material, the multidimensional hydrogen bond conductive binder and the conductive carbon black in 3-20 mL of water in a mass ratio of (60-85): (10-20): (5-20) to obtain a mixture; S2, coating the mixture in S1 on a copper foil current collector to obtain a pretreated electrode; S3. The pretreated electrode described in S2 is subjected to vacuum drying to obtain a silicon-carbon electrode.
9. The method for preparing a silicon-carbon electrode according to claim 8, characterized in that: The conductive carbon black in S1 is acetylene black or Super P; the coating thickness of the mixture in S2 is 100-150 μm, and the coating interval is 50-200 μm.
10. The method for preparing a silicon-carbon electrode according to claim 8, characterized in that: The vacuum degree of the vacuum drying in S3 is -60~-100 kPa, the temperature of the vacuum drying is 60~150°C, and the time of the vacuum drying is 1~12 hours.
Citation Information
Patent Citations
Crosslinking composite bonding agent and application thereof, lithium ion battery cathode material prepared on basis of bonding agent and preparation method of material
CN108470910A
Polyacrylate photo-curing adhesive and application thereof in silicon negative electrode plate of lithium ion battery
CN111234119A
Combined binder, preparation method thereof and application of combined binder in lithium battery
CN118516066A
Lithium-silicon battery comprising a silicon-carbon composite
US20240047650A1
Cited By
Silicon-carbon negative electrode slurry as well as preparation method and application thereof
CN119786538A
Silicon-carbon negative electrode slurry, preparation method and application thereof
CN119786538B
